The Real Estate Register: From the Personal Registration System to the Real Registration System: Algeria, Tunisia, Morocco as Models - BOUZITOUN, Abdelghani (Journal of Human Sciences, 2025)
The countries of the world have adopted the real estate registration system as a successful means to instill security, trust, and reassurance in real estate transactions. However, the implementation of this system within each country is subject to its capabilities and policies. Hence, two systems for real estate registration emerged in practice: the personal registration system, which relies on the names of individuals such as the owner and those with property rights, and was the first to appear. However, due to its shortcomings in addressing real estate issues, a new system emerged through "Robert Torrens," which is the title registration system, adopted by most countries around the world, including the countries of North Africa.  The land title registration system is characterized by its focus on the property itself rather than on individuals, ensuring greater accuracy in the preservation of property rights and limiting disputes. This system has contributed to enhancing trust in real estate transactions, as it provides a clear and accurate record of property rights, facilitating the process of trading and protecting the rights of the parties involved.